Effects of HIV diagnosis and enrolment in care on transmission risk of HIV-infected men who have sex with men in Hong Kong: a cross-sectional study. (October 2016) - Kwan, Tsz Ho; Poon, Chin Man; Wong, Ka Hing; Lee, Shui Shan
Abstract: Background: The HIV continuum of care is a framework for monitoring of health-care service targets. From a public health perspective, little is known about the changes of transmission risks of HIV-positive men who have sex with men (MSM) at different stages in the continuum. In this study we aimed to assess the effects of HIV diagnosis and enrolment in care on the transmission risk of HIV-infected MSM in Hong Kong. Methods: A questionnaire was administered to HIV-positive MSM attending the largest HIV specialist clinic in Hong Kong between October and December, 2014. Data collected included demographics, sex networking pattern, risk behaviours, and viral loads at different stages of the care continuum, following informed consent. Approval was obtained from Joint Chinese University of Hong Kong–New Territories East Cluster Clinical Research Ethics Committee (CREC). Findings: 345 HIV-positive MSM (median age 37 years, IQR 30–46) were recruited. Following diagnosis, sex networking through the internet and physical venues decreased, as shown by a fall in the number of visits by 14% and 23%, respectively, within a year. 74 (21%) men had no sex partners, with a median period of abstinence of 3–6 months. Consistent condom use for anal sex with regular and non-regular partners increased (p=0·001). 336 (97%) had initiated antiretroviral therapy either in the diagnosis year (160/336 [48%]) or subsequently. Viral load suppression was achieved 1 year after diagnosis (IQR 1–3 years), a status attained by 277 (80%) at the time of study. For those whose treatment were started more than 2 years before the survey (n=82), almost all (81 [99%]) had visited sex networking venues and 44 (54%) had engaged in unprotected anal sex within a year after treatment initiation. Interpretation: Diagnosis of HIV was associated with decreased sex networking and increased condom use. With the achievement of viral suppression in a majority of MSM, a general reduction of secondary HIV-transmission risk could be inferred. However, inconsistent condom use and sex networking after treatment initiation could predispose to the spread of sexually transmitted infections both within and between different MSM networks. Funding: Council for the AIDS Trust Fund, Hong Kong Special Administrative Region Government (project code MSS230R).